Hubungan Pengetahuan Remaja dan Status Ekonomi Keluarga dengan Kejadian Pernikahan Dini pada Remaja di Dusun Pintu Air Desa Simandulang Kec. Kualuh Leidong Tahun 2023 - Damayani Damayani; Khairunnisa Situmorang; Lasria Simamora; Yesica Geovany Sianipar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Early marriage can be defined as a registered or unregistered marriage where one or both partners are under the age of 19 years. Early marriage among teenagers tends to have a negative impact in terms of socio-economic, mental/psychological, physical, especially for the reproductive health of the teenager. This research aims to determine the relationship between adolescent knowledge and family economic status and the incidence of early marriage in Pintu Air Hamlet, Simandulang Village, Kualuh Leidong District in 2023. This type of research is an analytical survey with a cross-sectional research design. The population is all teenagers in Pintu Air Village Hamlet. Simandulang, Kualuh Leidong District as many as 63 people. The number of samples used was 63 people obtained using total sampling techniques. The data analysis technique uses chi square. The results obtained in this study were that most of the teenagers' knowledge was poor, with 24 respondents (38.1%) not marrying early, and most of the family's economic status was low, with 36 respondents (57.1%) not marrying early. Based on the results of the chi square test, there is a relationship between adolescent knowledge and the incidence of early marriage with a P value = 0.001 < 0.05 and there is a relationship between family economic status and the incidence of early marriage with a P value = 0.036 < 0.05 Conclusion: There is a relationship between adolescent knowledge and family economic status and the incidence of early marriage. Therefore, to reduce early marriage, the quality of education should be further improved.